Alternative for Gravel - Sanjika, B.; Mathivathanan, M.; Anburuvel, A. (ENGINEER, 2020)
Gravel is a commercial product with various applications; road construction is one of the main applications as more than 50% of gravel is used for road construction in Sri Lanka. The primary functions of gravel in road construction are providing structural support, improving drainage and reducing the intrusion of fine particles from the subgrade. Recent infrastructure developments in Northern Sri Lanka lead to over exploitation of gravel for various purposes which have made the gravel deposits to decrease drastically. The absence of gravel brought many road construction projects to a halt. Available replacements for gravel such as aggregate base course are costly. To find alternative solutions for material shortage, research studies have been conducted on constructing pavements with stone dust, Fly Ash (FA), Waste Recycled Products (WRP), Construction and Demolition waste (CDW), Recycled Asphalt Pavement (RAP) plastic fibers/strips, scrap tyres, and geosynthetics, instead of conventional materials. This study aims to explore the alternative options to overcome gravel scarcity in Northern Sri Lanka by replacing conventional road construction materials. This paper examines the usage of locally available soil in the region reinforced with waste plastic, waste aggregate and geogrid as a replacement for road construction material instead of gravel. Series of California Bearing Ratio (CBR) tests were conducted on locally available soil reinforced with said materials to find the best alternative pavement construction material in Northern Sri Lanka. Preliminary investigations revealed that placing geogrids between layers of local soil horizontally (transverse to the direction of loading) improves CBR value of local soil significantly. Plastic strips were also found to be effective in improving the CBR values. For immediate replacement for gravel, geogrids are relatively economical over aggregate base course. By reusing waste material, this study promotes an alternative method to mitigate the environmental problems.
Keywords: California Bearing Ratio; Geosynthetics; Gravel